2017
DOI: 10.1063/1.4979289
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir wave filamentation in the kinetic regime. I. Filamentation instability of Bernstein-Greene-Kruskal modes in multidimensional Vlasov simulations

Abstract: A nonlinear Langmuir wave in the kinetic regime kλD 0.2 may have a filamentation instability, where k is the wavenumber and λD is the Debye length. The nonlinear stage of that instability develops into the filamentation of Langmuir waves which in turn leads to the saturation of the stimulated Raman scattering in laser-plasma interaction experiments. Here we study the linear stage of the filamentation instability of the particular family [1] of Bernstein-Greene-Kruskal (BGK) modes [2] that is a bifurcation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…(2) There is a small damping (and frequency shift) acting on DNS, an effect that we attribute to the numerical dissipation well known in Vlasov simulations [36,37]. We confirm this hypothesis in Sec.…”
Section: B Comparison Between Direct Numerical Simulations and The Rsupporting
confidence: 78%
“…(2) There is a small damping (and frequency shift) acting on DNS, an effect that we attribute to the numerical dissipation well known in Vlasov simulations [36,37]. We confirm this hypothesis in Sec.…”
Section: B Comparison Between Direct Numerical Simulations and The Rsupporting
confidence: 78%
“…i) The agreement is good, both in terms of frequency and amplitude, over fairly long time scales. ii) There is a small damping (and frequency shift) acting on the direct numerical simulation (DNS), an effect that we attribute to the numerical dissipation well known in Vlasov simulations [29,30]. We confirmed that hypothesis by varying grid sizes (see SM [24]).…”
supporting
confidence: 78%
“…For σ > 2 one can interpret the term −νΛ σ ω in (1) as a hyperviscosity which is widely used in many applications, see e.g. [38], where hyperviscosity is employed in high temperature plasmas.…”
Section: Introductionmentioning
confidence: 99%